Oportunidades e ameaças de Bolonha (um processo em curso) e a universidade europeia (um projecto em discurso) num contexto de globalização - Amélia Veiga (2003)
The establishment of a european higher education area is a defensible objective and shall be discussed hereafter as far as the tools used for its implementation are concerned. The effects of globalisation might force the harmonisation of higher education systems, which on its turn may lead to the commodification of education when considering its utmost principles. In this case, competitiveness in higher education may be limited to the price to be paid in the education market. Under these circumstances, several scenarios shall be considered which enable the enhancement of competitiveness and attractiveness of the european higher education area, preserving however the diversity and differentiation of the european higher education systems.Considering that the Bologna process casts doubt on its consequences, especially as far as the preparation of higher education institutions to the challenges of globalisation is concerned, we seek to provide a range of analyses that enable us to study the strengths and weaknesses of the Bologna process from a systemic perspective.The creation of a european higher education area being regarded as one leap towards the european integration, it is vital to understand whether the Bologna process provides the european universities with an adequate answer that enables them to interact with the new globalisation paradigm for the definition of higher education policies.